Perancangan Sistem Informasi Inventaris Barang Berbasis Web - Antonius Oko Pranoto; Eko Sediyono (Jurnal Teknik Informatika dan Sistem Informasi, 2021)
Information technology is rapidly developing and applied in any field of interest. It can be used as simple to the complex computation. It can also use greatly assisting human performance in managing inventory items. This paper discusses a website-based item inventory system applied in a very remote village in Desa Kusik Batu, West Kalimantan. The research goal is to facilitate the performance of village officials in managing data items, where overall data input is still done manually. The method of this research is using interviews, documentation, and literature studies. The implementation of the system resulted from this research is the following features: user data, all goods data having by the village, incoming goods data, outgoing goods data, avoid physical calculations, asset mutation reports, and goods reports, as well as making goods inventory reports can be easily done. With the existence of a web-based inventory information system website, at the village office of Kusik Batu Lapu, West Kalimantan, can improve the performance of village officials to manage goods data.